A simple and fast sample preparation method based on ionic liquid treatment for determination of Cd and Pb in dried solid agricultural products by graphite furnace atomic absorption spectrometry. (May 2021) - Ling, Yuetao; Luo, Fang; Zhu, Shengdong
Abstract: The Cd and Pb are two typical heavy metal contaminants of agricultural products which have posed great threats to human health. The precise determination of Cd and Pb in agricultural products is extremely important for human health. In this paper, a simple and fast sample preparation method based on ionic liquid treatment was proposed to determine Cd and Pb in dried solid agricultural products by graphite furnace atomic absorption spectrometry (GFAAS). The samples were prepared by dissolving the tested agricultural products into the ionic liquid 1-butyl-3-methylimidazolium chloride. The temperature program and matrix modifiers for GFFAS analysis of these samples were optimized. The reliability of sample preparation was verified by comparing the between- and within-batch precision, which showed no significant differences at 95% confidence level. Detection limits were 0.019 μg L −1 Cd and 0.042 μg L −1 Pb for these samples. Results for determining Cd and Pb in these samples were in good agreement with those obtained from the conventional wet digested samples. Both the certified reference materials validation experiments and the spiked and recovery tests indicated this sample preparation for determining Cd and Pb had satisfactory accuracy and could be an alternative to traditional sample preparation. Highlights: A new sample preparation method based on ionic liquid treatment was developed. ≫Conditions for sample preparation and GFAAS analysis of Cd and Pb were optimized. ≫Its reliability and accuracy were verified by three standard methods. ≫It could be used for precise analysis of Cd and Pb in agriculture solid samples.